Changes in the association between job decision latitude and work engagement at different levels of work experience: A 10-year longitudinal study. Issue 2 (2nd April 2020) - Heinrichs, Katherina; Angerer, Peter; Li, Jian; Loerbroks, Adrian; Weigl, Matthias; Müller, Andreas
ABSTRACT: This study set out to explore the effects of accumulating work experience on the association between job decision latitude and its interaction with job demands and work engagement. Our ten-year longitudinal study followed 333 junior physicians in postgraduate training at baseline. We used self-report measures in four assessment waves, and we conducted path analyses to investigate linear and curvilinear regression effects. Results show that high job decision latitude was associated with high work engagement at all levels of work experience, with strongest associations at baseline and after ten years. Only for novices did job decision latitude buffer the negative association between job demands and work engagement. At the stage of high work experience, low levels of job decision latitude were weakly associated with work engagement, whereas with higher levels of job decision latitude, the positive association seemed to strengthen. Our findings indicate that job decision latitude is a key job resource at all stages of work experience, with stronger effects among novices and experts. Organisations' work design efforts should include job decision latitude to promote work engagement across employees' different career stages, with consideration to job entrants and experts in order to tailor specific work design solutions.